Effectiveness of sulfuryl fluoride for control of different life stages of stored-product psocids (Psocoptera) - Athanassiou, Christos G.; Phillips, Thomas W.; Aikins, Michael J.; Hasan, M. Mahbub; Throne, James E. (My University, 2012)
With the phase-out and impending ban of methyl bromide, sulfuryl fluoride is among the most promising alternative fumigant insecticides for control of stored-product insect pests. It has been evaluated for control of several stored-product insect pests, but there are few data available on its efÞcacy for control of stored-product psocids (Psocoptera). We evaluated sulfuryl ßuoride for control of different life stages of the psocids Liposcelis paeta Pearman, L. entomophila (Enderlein), L. bostrychophila Badonnel, L. decolor Pearman, and Lepinotus reticulatus Enderlein (Trogiidae) in 48-hr trials at 27.5 C. Adults and nymphs were susceptible to sulfuryl fluoride. Complete (100%) adult and nymphal mortality was recorded at concentrations between 4 and 8 g/m3, except for L. decolor for which all adults were only killed at 24 g/m3. Eggs were tolerant to sulfuryl fluoride. Complete egg mortality was achieved at 24 and 72 g/m3 for L. reticulatus and L. decolor, respectively. Survival of L. paeta eggs was recorded even after exposure to 96 g/m3. Given that the highest United States label concentration for sulfuryl fluoride for a 48-h exposure interval is 31.25 g/m3, our study indicates that high doses and/or longer exposures are needed for complete mortality of eggs of L. decolor and L. paeta. Moreover, the present work suggests that there is considerable variation in efÞcacy of sulfuryl fluoride for control of different psocid species.

Citation: Athanassiou, Christos G., Thomas W. Phillips, M. Jamie Aikins, M. Mahbub Hasan, and James E. Throne. 2012. “Effectiveness of Sulfuryl Fluoride for Control of Different Life Stages of Stored-Product Psocids (Psocoptera).” Journal of Economic Entomology 105 (1): 282–87. https://doi.org/10.1603/EC11209.
Keywords: Sulfuryl fluoride; Fumigation; Psocoptera; Liposcelis; Lepinotus